(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Non-communicable diseases, which account for more than 60% of all deaths globally include Cardiovascular Disease (CVD), various cancers, chronic disorders, and diabetes. In India, the age-standardized CVD death rate is 272 per 100,000 people, which is much higher than the global average of 235. The aim of this five-year retrospective cross-sectional study carried out at a tertiary care hospital in Western Maharashtra from Oct 2018 to Oct 2023, is to understand the prevalence and etiology of sudden cardiac deaths. The data were obtained retrospectively from medico-legal autopsy reports and inquest papers, tabulated systematically and analysed statistically. During the study period, a total of 1200 post-mortems were conducted, out of which 24.83% of cases are of SCD. 22.82% of cases are of 51 to 60 years, and 75.84% are of males with a Male: Female ratio of 3:1. 74.83% are from urban areas with an Urban: Rural ratio of 3:1. 90.27% of SCDs are due to Coronary Artery Disease (CAD) while 57.05% of these cases have no comorbidities. Male preponderance of 44.97% is seen across all age groups and comorbidities. The prevalence of SCDs among adult males of 50 to 70 years is eyebrow raising in this part of the country. The etiology of SCDs is found to be multifactorial with or without a history of previous comorbidities present in the patients, with CAD being a major factor. Maintaining a healthy non sedentary lifestyle is the way forward to reduce the incidences of SCDs.